1983
DOI: 10.1103/physrevlett.51.1286
|View full text |Cite
|
Sign up to set email alerts
|

Defect Symmetry from Stress Transient Spectroscopy

Abstract: Uniaxial stress has been used with transient spectroscopy to study the level at E c -0.17 eV in neutron-irradiated silicon. The defect symmetry, observed stress-induced electronic redistribution, and preferential stress-induced defect orientation have been determined and the reorientation activation energy has been measured. All of these effects are consistent with the A center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 6 publications
2
12
0
2
Order By: Relevance
“…The symmetry of VO has been also confirmed by the DLTS measurements combined with the uniaxial stress [2], and recently by the highresolution Laplace DLTS method [10]. The Laplace DLTS peak splitting pattern for the uniaxial stress applied along the main crystallographic directions agrees with the orthorhombic defect symmetry as found in Ref.…”
Section: 3supporting
confidence: 57%
See 2 more Smart Citations
“…The symmetry of VO has been also confirmed by the DLTS measurements combined with the uniaxial stress [2], and recently by the highresolution Laplace DLTS method [10]. The Laplace DLTS peak splitting pattern for the uniaxial stress applied along the main crystallographic directions agrees with the orthorhombic defect symmetry as found in Ref.…”
Section: 3supporting
confidence: 57%
“…When the defect is in the neutral charge state the effective barrier for reconfiguration of the oxygen atom is 0.38eV [2,9,10]. It has been observed that this barrier is reduced by the stress when the stress is applied along the <100> direction.…”
Section: 3mentioning
confidence: 97%
See 1 more Smart Citation
“…Among the first successful applications were the celebrated modeling by Watkins and Corbett 84 and Corbett et al 85 of vacancy-oxygen center (VO) in silicon by EPR and local-mode IR spectroscopy. The center was studied also in early applications of hydrostatic and uniaxial-stress DLTS by Samara 86 and by Meese, Farmer, and Lamp, 87 respectively. The comparison of VO stress data from different experimental techniques reveals features in analysis and interpretation that may be considered as textbook examples.…”
Section: Piezospectroscopic Parameters From Alignment Studiesmentioning
confidence: 99%
“…This technique has been applied [239] to the A-centre, or V-O centre in Si, which is known to have C 2v symmetry [240]. To our knowledge, this technique has only been applied to investigate the symmetry of one TM-related centre in silicon [241].…”
Section: -Levelsmentioning
confidence: 99%